(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper seeks to illustrate the observation from studies on second language acquisition and use that culture-specific aspects of a given language can be adapted to the norms of the culture of the linguistic community that widely uses it as a second language. Specifically, the paper looks at how written requests are made in Kenyan English with reference to how they are in British English, its direct ancestor. It bases its discussion and conclusion on two types of data: a) judgment data in the form of preference choices in terms of which request formulas are most likely to be used by a sample of a hundred and eleven respondents; b) production data in the form of nonelicited requests actually made to the author by his students. In both cases, the subjects were University of Nairobi students. The frequency counts of which requests would most likely be used and of those which were actually used show the request structures used in Kenyan English to be shorter and more limited in number than those in British English.